Time-Dependent Restoration Routing Problem: An Efficient Initial Solution - Saviz Saei; Nazanin Tajik (Findings)
We propose a time-dependent variant of the restoration routing problem scheduling restoration tasks for each crew given a limited time horizon. The model provides a feasible initial solution for real-world restoration crew routing problems. We also acknowledge the effect of topological characteristics on the network resilience enhancement during the restoration process.